INOVASI NADIEM MAKARIM MENGENAI MERDEKA BELAJAR - Resti Lathifah; Tiara Maharani, Salma Pratiwi Agustin, Fitha Chaerunisa, Wella Mada Septian, Esla Rahayu Setianingsi (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2022)
Education is a conscious and planned effort to create a learning atmosphere and learning process so that students actively develop their potential to have religious spiritual strength, self-control, personality, intelligence, noble character, and the skills needed by themselves, society, nation and country. Freedom to learn is defined as freedom to think, freedom to innovate, freedom to learn independently and creatively, and freedom for happiness. The concept of independent learning is initiated so that students have freedom in thinking critically and intelligently, this will make students explore how the educational process is meant by Ki Hadjar Dewantara in implementing Ing Ngarso Sung Tuladha, Ing Madya Mangun Karso, and Tut Wuri Handayani in the current education system in Indonesia promotes openness in thinking. Four policy points in independent learning: 1. National Standard School Examination (USBN), 2. National Examination (UN), 3. Learning Implementation Plan (RPP), and 4. Zoning Regulations for Admission of New Students (PPDB).